PALEOGENE PLANKTONIC FORAMINIFERS AND STRATIGRAPHY OF THE OBRUCHEV RISE (NORTHERN PACIFIC) - Basov I.A. (My University, 1997)
The taxonomic composition of planktonic foraminifers from the relatively complete Paleogene sections first recovered by deep-sea drilling in high latitudes of the North Pacific allowed these deposits to be dated and subdivided. In its composition and morphological peculiarities, the Paleogene assemblage of planktonic foraminifers from the Obruchev Rise is similar to that from coeval deposits in high-latitude areas of the Earth: the Crimea-Caucasus and Koryak-Kamchatka regions in the northern hemisphere, and from the Campbell, Kerguelen, and Falkland plateaus and New Zealand in the southern hemisphere. Based on the distribution of the planktonic foraminiferas, only major stratigraphic units of the subseries rank can be distinguished in the Paleogene section of the Obruchev Rise, whereas the lower Eocene interval can be subdivided into zonal units of the Crimea-Caucasus biostratigraphic scale. Changes in the foraminifera composition generally reflect global climatic fluctuations inferred worldwide by paleontologic and isotopic studies.
Keywords: Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген